Pengaruhnkompetensinkaryawan, Disiplinnkerja Dan Motivasinkerja Terhadapnkinerja Karyawanndi PDAM Kabupaten Indramayu - Fetty Poerwita Sary; Zidan Ruhul Hayat (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Thisnstudy aimsnto determinenhow the influencenof employee competence, work discipline and work motivation on employeenperformance conducted at the Indramayu Regency PDAM Office. This researchnis includednin the typenof quantitativenresearch. The research method used is multiplenlinear regressionnanalysis usingnSPSS Software Version 26 and descriptive analysis techniques. Basednon the processing results, itnis knownnthat employee competence, work discipline and work motivation partially and simultaneously affect employee performance. Thencoefficient ofndetermination isnknown thatncompetence, work discipline and work motivation have an effect of 64.7% on the performance of PDAM Indramayu Regency employees, while the remaining 35.3% are influenced by other variables not included in this study such as compensation, work environment, etc. other. So to improve employee performance, namely by paying attention to and improving employee competence, work discipline and work motivation properly will be able to helpnimprove employee performance.nHigh performancemhelps organizationsmobtain resultsmthat meet expectationsnand achieve organizationalngoals Keywords: employee performance, competence, work discipline, motivation.